Safety and Immunogenicity of the Ad26.RSV.preF Investigational Vaccine Coadministered With an Influenza Vaccine in Older Adults. (26th August 2020) - Sadoff, Jerald; De Paepe, Els; Haazen, Wouter; Omoruyi, Edmund; Bastian, Arangassery R; Comeaux, Christy; Heijnen, Esther; Strout, Cynthia; Schuitemaker, Hanneke; Callendret, Benoit
Abstract: Background: Respiratory syncytial virus (RSV) and influenza cause significant disease burden in older adults. Overlapping RSV and influenza seasonality presents the opportunity to coadminister vaccines for both infections. This study assessed coadministration of the investigational vaccine, Ad26.RSV.preF, an adenovirus serotype 26 (Ad26) vector encoding RSV F protein stabilized in its prefusion conformation (pre-F), with a seasonal influenza vaccine in older adults. Methods: In this phase 2a, double-blind, placebo-controlled study, 180 adults aged ≥60 years received Ad26.RSV.preF plus Fluarix on day 1 and placebo on day 29, or placebo plus Fluarix on day 1 and Ad26.RSV.preF on day 29 (control). Results: The coadministration regimen had an acceptable tolerability profile. Reactogenicity was generally higher after Ad26.RSV.preF versus Fluarix, but symptoms were generally transient and mild or moderate. At 28 days after the first vaccination, the upper confidence intervals of the hemagglutination inhibition antibody geometric mean ratio (control/coadministration) for all influenza strains were <2, demonstrating noninferiority. Robust neutralizing and binding antibody responses to RSV A2 were observed in both groups. Conclusions: Coadministration of Fluarix with Ad26.RSV.preF vaccine had an acceptable safety profile and showed no evidence of interference in immune response. The results are compatible with simultaneous seasonal vaccination with both vaccines. Clinical Trials Registration: NCT03339713. Abstract : Coadministration of Fluarix with the Ad26.RSV.preF vaccine had an acceptable safety profile and showed no evidence of interference in immune response in healthy adults aged ≥60 years.